Post-Retirement Challenges: A Study of Gurkha’s Families - Basnet, Sushil (Aadim Journal of Multidisciplinary Research, 2025)
This article explores the difficulties faced by retired Singapore Gurkhas and their families when they return to Nepal after many years of service abroad. Unlike British or Indian Gurkhas, this study focuses only on those who served in Singapore. It provides background information about the Gurkhas and collects data through interviews and other sources. The study highlights the emotional, social, and practical challenges experienced by the retirees and their families. It emphasizes the need for policies and support systems to help them live a dignified and comfortable life after retirement.